Frequency of Depression in Patients with Conversion Disorder - Abid Ul Abrar; Ahmed, Waqas; Habib Ullah; Sohail, Amir; Adnan, Mian Sohail (Indus Journal of Bioscience Research, 2025)
Objectives: To determine the frequency of depression in patients with conversion disorder in Ayub Teaching Hospital Abbottabad. Study Design: Cross sectional (descriptive) study. Place and duration of the study: The study was carried out in the Department of Psychiatry of Ayub Teaching Hospital Abbottabad from 1st June to November 2024. Methodology: The study population was included, all patients of depression diagnosed with conversion disorder with age between 10 to 70 years of either gender and depression was graded as per operational definition. Results: The sample size (N) for the age variable is 92, with ages ranging from a minimum of 10 years to a maximum of 70 years. The mean age of patients is 37.98 years, with a standard deviation of 18.427 years. The gender distribution among patients shows that 31 patients (33.7%) are male, while 61 patients (66.3%) are female. The total sample size for gender is 92. In terms of depression status, 37 patients (40.2%) are classified as normal, whereas 55 patients (59.8%) are classified as having depression. The total sample size for depression status is 92. Conclusion; The study highlights a substantial prevalence of depression among patients diagnosed with conversion disorders, with 59.8% of the sample exhibiting depressive symptoms.